2023
DOI: 10.1007/s43657-023-00128-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenomic Imaging

Lizhen Lan,
Kai Feng,
Yudan Wu
et al.

Abstract: Human phenomics is defined as the comprehensive collection of observable phenotypes and characteristics influenced by a complex interplay among factors at multiple scales. These factors include genes, epigenetics at the microscopic level, organs, microbiome at the mesoscopic level, and diet and environmental exposures at the macroscopic level. “Phenomic imaging” utilizes various imaging techniques to visualize and measure anatomical structures, biological functions, metabolic processes, and biochemical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…Among them, ultrasound elastography (UE) is an emerging ultrasound-based modality for in vivo imaging that has been used for visualization of tissue elasticity. In addition to variations of biomolecular expression, elasticity or stiffness of tumor tissues is also an important “physical” marker to distinguish malignant tumors from normal or stromal tissues . Compared to the current standards of B-mode ultrasound and aspiration biopsy approach, differentiating the various benign or malignant tumors using UE proves to have more outstanding performance in tumor location and diagnostic accuracy for breast, thyroid, and prostatic lesions analysis. , It is reported that the UE technique is used for prognostication of neoadjuvant chemotherapy response in different models with high specificity, providing a great potential for active detecting of tumor response to drug treatment, such as locally late-stage breast cancer as early as 2 weeks into treatment, IBC, and murine breast cancer model treated by chemotherapy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, ultrasound elastography (UE) is an emerging ultrasound-based modality for in vivo imaging that has been used for visualization of tissue elasticity. In addition to variations of biomolecular expression, elasticity or stiffness of tumor tissues is also an important “physical” marker to distinguish malignant tumors from normal or stromal tissues . Compared to the current standards of B-mode ultrasound and aspiration biopsy approach, differentiating the various benign or malignant tumors using UE proves to have more outstanding performance in tumor location and diagnostic accuracy for breast, thyroid, and prostatic lesions analysis. , It is reported that the UE technique is used for prognostication of neoadjuvant chemotherapy response in different models with high specificity, providing a great potential for active detecting of tumor response to drug treatment, such as locally late-stage breast cancer as early as 2 weeks into treatment, IBC, and murine breast cancer model treated by chemotherapy …”
Section: Introductionmentioning
confidence: 99%
“… 18 Compared to the current standards of B-mode ultrasound and aspiration biopsy approach, differentiating the various benign or malignant tumors using UE proves to have more outstanding performance in tumor location and diagnostic accuracy for breast, 19 21 thyroid, and prostatic lesions analysis. 22 , 23 It is reported that the UE technique is used for prognostication of neoadjuvant chemotherapy response in different models with high specificity, providing a great potential for active detecting of tumor response to drug treatment, such as locally late-stage breast cancer as early as 2 weeks into treatment, 19 IBC, 20 and murine breast cancer model treated by chemotherapy. 21 …”
Section: Introductionmentioning
confidence: 99%
“…Although standing cervical spine X-rays are economically feasible and readily available, they are limited to two-dimensional images with suboptimal resolution (Azimi et al, 2021;Boudreau et al, 2021). In contrast, MRI, being non-invasive and free from ionizing radiation risks, provides a more comprehensive evaluation of sagittal balance (Lan et al, 2023). However, supine MRI may not accurately reflect the loading state of the cervical spine in an upright posture, potentially leading to measurement inaccuracies (Boudreau et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although the gold standard for evaluating TILs is based on routine haematoxylin–eosin (H&E) staining using a semi-quantitative scoring method, it may be subject to interobserver variability and costly [ 19 ]. Computational pathology has currently displayed promise in recognizing the biomarkers in tissues, and overcomes limitations related with manual grading and human bias [ 20 ]. Therefore, we establish cellular training sets for AEGJ, GAC, and ESCC based on the assessment of experienced pathologists.…”
Section: Introductionmentioning
confidence: 99%